Haman a biography - Silverstein, Adam ca. 20./21. Jh. (Princeton Oxford Princeton University Press, 2025)
"The first book-length study of the biblical villain Haman, examining his depiction across Judaism, Christianity, and Islam. Haman, infamous as the antagonist in the book of Esther, appears as a villainous figure in virtually all varieties of Judaism, Christianity, and Islam. In this "biography" of Haman, Adam Silverstein traces the evolution of this villainous character from the ancient Near East to modern times, drawing on sources in a variety of languages and from diverse genres. Silverstein considers the evidence for a historical Haman and analyzes the abundance of material that that documents what those who read the Bible and the Qur'ān have thought about him over the past two millennia.With this book, Silverstein offers an essential and original account of the rich diversity and openness of Abrahamic civilizations throughout history. Taking Haman as a case study, Silverstein guides the reader through diverse intellectual terrains, covering ancient Near Eastern cultures, pre-Islamic Iranian literature, Abrahamic scriptures and their interpretation, late antiquity, Islamic history, and interfaith relations. He shows how the figure of Haman has both united and divided Jewish, Christian, and Muslim communities, who collaborated fruitfully in their efforts to grasp the meaning and significance of their holy books, but who also deployed the "Haman" label polemically against each other. Silverstein also considers Haman's prebiblical origins, raising the possibility that the book of Esther was receiving and reconfiguring Haman no less than later works were, with Esther's villain taking his place in a long line of reimagined Hamans.Haman: A Biography is the first book-length study to contextualize an Abrahamic character not only within Jewish and Christian traditions but also with reference to the character's prebiblical background and reception in Islamic cultures"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Haman -- (Biblical figure); SOCIAL SCIENCE / Jewish Studies; SOCIAL SCIENCE / Islamic Studies